Effects of bicuculline application on the somatosensory responses of secondary vestibular neurons. (29th October 2016) - Grasso, C.; Li Volsi, G.; Cataldo, E.; Manzoni, D.; Barresi, M.
Highlights: GABA A antagonist application modifies secondary vestibular neurons resting and somatosensory-evoked activity. Units showing an increased resting discharge can either increase or decrease their somatosensory responsiveness. In about a third of the neurons, the responsiveness changes without modifications in resting discharge. Occasionally, depression in basal activity and responsiveness can be observed in the same unit. It is possible that forepaw rotation modulates GABA release at the level of secondary vestibular neurons. Abstract: Limb somatosensory signals modify the discharge of vestibular neurons and elicit postural reflexes, which stabilize the body position. The aim of this study was to investigate the contribution of the γ-amino-butyric-acid (GABA) to the responsiveness of vestibular neurons to somatosensory inputs. The activity of 128 vestibular units was recorded in anesthetized rats in resting conditions and during sinusoidal foreleg rotation around the elbow or shoulder joints (0.026–0.625 Hz, 45° peak amplitude). None of the recorded units was influenced by elbow rotation, while 40% of them responded to shoulder rotation. The selective GABAA antagonist receptor, bicuculline methiodine (BIC), was applied by microiontophoresis on single vestibular neurons and the changes in their activity at rest and during somatosensory stimulation was studied. In about half of cells the resting activity increased after the BIC application: 75% of these neurons showed also an increased response to somatosensory inputs whereas 17% exhibited a decrease. Changes in responsiveness in both directions were detected also in the units whose resting activity was not influenced by BIC. These data suggest that the responses of vestibular neurons to somatosensory inputs are modulated by GABA through a tonic release, which modifies the membrane response to the synaptic current. It is also possible that a phasic release of GABA occurs during foreleg rotation, shaping the stimulus-elicited current passing through the membrane. If this is the case, the changes in the relative position of body segments would modify the GABA release inducing changes in the vestibular reflexes and in learning processes that modify their spatio-temporal development.